2021
DOI: 10.3389/fimmu.2021.609644
|View full text |Cite
|
Sign up to set email alerts
|

Prevotella histicola Protects From Arthritis by Expansion of Allobaculum and Augmenting Butyrate Production in Humanized Mice

Abstract: Bacterial therapeutics are the emergent alternatives in treating autoimmune diseases such as Rheumatoid Arthritis [RA]. P. histicola MCI 001 is one such therapeutic bacterium that has been proven to treat autoimmune diseases such as RA and multiple sclerosis [MS] in animal models. The present study characterized P. histicola MCI 001 isolated from a human duodenal biopsy, and evaluated its impact on the gut microbial and metabolic profile in a longitudinal study using the collagen-induced arthritis model in HLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 76 publications
0
43
0
1
Order By: Relevance
“…The role of SCFAs in suppressing systemic inflammation has been widely recognized, particularly in rheumatoid arthritis (Ang & Ding, 2016; Durholz et al, 2020). We believe that the effect of improving arthritis is the result of a combination of SCFAs, with butyrate being the most effective (Bai et al, 2021; Balakrishnan et al, 2021; Wen et al, 2020). Therefore, adding dietary fibre to the diet to increase the level of SCFAs may be an effective strategy for the treatment of rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…The role of SCFAs in suppressing systemic inflammation has been widely recognized, particularly in rheumatoid arthritis (Ang & Ding, 2016; Durholz et al, 2020). We believe that the effect of improving arthritis is the result of a combination of SCFAs, with butyrate being the most effective (Bai et al, 2021; Balakrishnan et al, 2021; Wen et al, 2020). Therefore, adding dietary fibre to the diet to increase the level of SCFAs may be an effective strategy for the treatment of rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…in the gut has a robust capacity to produce acetate, which is the main substrate for some SCFAs synthesis. This strain is a well-known SCFAs-producing bacteria (Tian et al, 2020 ; Balakrishnan et al, 2021 ). The relative abundance of Allobaculum was significantly decreased in the mice with depression-like behaviors, but restored after treatment with 5-HTP.…”
Section: Discussionmentioning
confidence: 99%
“…At the genus level, the LMet group also showed a significant increase in Prevotella and Rikenellaceae_ RC9 ( Figure 4 ). Studies have shown that Prevotella was able to generate short-chain fatty acids, mainly acetic acid, through the degradation of carbohydrates [ 67 ], and that high levels of Prevotella enhanced the fermentation of complex polysaccharides and improved glucose metabolism [ 68 ], which explained the rise in acetic acid production in the LMet group. In addition, Balakrishnan B et al suggested that Prevotella maintained the stability of the immune system by enhancing butyrate production [ 67 ], which was consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Prevotella was able to generate short-chain fatty acids, mainly acetic acid, through the degradation of carbohydrates [ 67 ], and that high levels of Prevotella enhanced the fermentation of complex polysaccharides and improved glucose metabolism [ 68 ], which explained the rise in acetic acid production in the LMet group. In addition, Balakrishnan B et al suggested that Prevotella maintained the stability of the immune system by enhancing butyrate production [ 67 ], which was consistent with the results of this study. Furthermore, Zhao et al suggested that Rikenellaceae_ RC9 positively correlated with the production of total volatile fatty acids and acetic acid, while affecting the pH of rumen fluid [ 69 ].…”
Section: Discussionmentioning
confidence: 99%